A Novel Algorithm for Optimal Harmonic Load Flow including Harmonic Compensation - Godbole, Prachi; George, Sincy (Engineering, Technology & Applied Science Research, 2023)
Load flow analysis is widely used for finding voltage at various parts of a large, interconnected power system. The exponential increase in the use of power electronic devices and the noticeable percentage of integration of renewable energy sources in modern power systems result in the occurrence of non-sinusoidal voltages at various parts of the power system. By reformation of the Newton-Raphson load flow method, a few harmonic load flow algorithms have been developed for modern transmission systems. However, for larger transmission systems, complexity and heavy computational burden are often encountered in the load flow solution process due to the increased size of the Jacobean matrix that further increases with multiple non-linear load buses and compensation requirements. This leads to convergence problems and increased execution time. In this paper, an optimal harmonic load flow algorithm is proposed, that employs a modified PSO technique to select control variables and the harmonic load flow method to find solutions for load flow analysis with a reduced size of the Jacobean matrix. The formulated method uses a simple technique to take into account nonlinear loads and results in faster convergence. The novelty of the algorithm is that an optimal load flow solution with the desired amount of reactive and harmonic compensation currents is obtained. The algorithm can help in getting load flow solutions in future power systems with distorted voltage and currents with compensation. The performance of the proposed algorithm is tested on a modified IEEE 30-bus system with multiple non-linear load buses and is validated with the Simulink model of the system.